Shortening surgical time in high myopia treatment: a randomized controlled trial comparing non-OVD and OVD techniques in ICL implantation - Muhammad Ahmad Khan; Saif Ur Rehman Khan; Ding Lin (BMC Ophthalmology)
Abstract Introduction High myopia correction is essential for improving visual acuity and quality of life. Traditional intraocular collamer lens (ICL) implantation using an ophthalmic viscosurgical device (OVD) is effective but often results in prolonged surgical times, impacting patient comfort and recovery. This study investigates a novel non-OVD ICL implantation technique aimed at reducing surgical duration and improving patient outcomes. Methods This prospective, randomized controlled trial was conducted at Changsha Aier Eye Hospital from May to August 2024, enrolling 162 right eyes from high myopic patients aged 21 to 45 years. Participants were randomly assigned to either the non-OVD group, which utilized a disposable sterile irrigator for anterior chamber maintenance, or the OVD group, which underwent traditional ICL implantation. Primary outcomes included surgical time, endothelial cell density (ECD), intraocular pressure (IOP), and patient-reported experiences. Results The non-OVD group demonstrated a significant reduction in surgical time (113 ± 103 s) compared to the OVD group (436 ± 118 s, p < 0.001). ECD and IOP remained stable postoperatively, indicating no adverse effects on ocular health. Patient experiences were assessed through pain levels and self-perception reports; the non-OVD group reported comparable pain levels with enhanced self-perception compared to the OVD group. Conclusion The novel non-OVD ICL implantation technique significantly reduces surgical duration while maintaining ocular health and improving patient self-perception. Additional to it, we also explored patients' self-perception, which refers to their subjective evaluation of recovery, well-being, and visual outcomes post-surgery. Unlike satisfaction, which primarily measures how pleased patients are with the results, self-perception encompasses how patients feel about their overall recovery process, including psychological and emotional factors. This approach may enhance operational efficiency and patient comfort in high myopia surgeries. Trial registration The study was registered with the China Clinical Trial Registration Center (Registration No. ChiCTR2100046483, Trial Registration: 2021–03-06).